The Overview of the Effectiveness of Infrared on the Healing Rate of Incision and Burn Wounds in Male White Rats - Ama, Fuad; Purbowati, Rini; Rianti, Emillia Devi Dwi (Electronic Journal of Education, Social Economics and Technology, 2024)
Infrared rays have low energy and their use does not cause toxic effects on the environment, so that infrared rays can balance and activate cells in the body, thin the blood, break down water molecules, and inhibit bacteria or fungi. Inhibition of bacterial or fungal growth in skin wounds that are often experienced and cause damage to epithelial tissue. The purpose of the study provides an overview of the effectiveness of infrared on the healing rate of incision wounds and burns in Wistar rats. The method with an experiment with a completely randomized design method, the sample used was 48 male white rats with 24 with incision wounds and 24 with burns. The results of the incision wound on the 12th day showed that there was a reduction in the length of the wound at P1 (0.1 cm), P2 (0.1 cm) and P3 (0.2 cm) so that with a wound length of 0.1 means healing has occurred. Burns on the 12th day there was a decrease in the diameter of the burn wound both at P1 = P2 = P3 = 0.3 cm. Conclusion The use of infrared therapy in the healing process of incision wounds and burns on days 9-12. Infrared wavelength 940 nm as near infrared produces heat, so the healing process is less than 14 days.